Yabancı Dil Hazırlık Eğitimi Alan Öğrencilerin Yabancı Dile Yönelik Kaygı ve Başarıları Arasındaki İlişkiler - Tuncer, Murat; Temur, Mehmet (Dicle Üniversitesi, 2017)
Bu araştırmanın amacı İngilizce hazırlık eğitimi alan öğrencilerin yabancı dil ders kaygısına yönelik görüşlerinin değerlendirilmesidir. Araştırma tarama modeline göre yürütülmüştür. Araştırmada Horwitz, Horwitz ve Cope (1986) tarafından geliştirilen ve geçerlik-güvenirlik çalışması Gürsu (2011) tarafından yapılan İngilizce Dersine Yönelik Kaygı ölçeği kullanılmıştır. Araştırmanın evrenini İnönü Üniversitesi Yabancı Diller Yüksekokulu bünyesinde yabancı dil hazırlık eğitimi alan lisans öğrencileri oluşturmaktadır. Araştırmada örneklem seçimi yoluna gidilmemiş, veri toplama araçlarının uygulandığı dönemde sınıflarında hazır bulunan bütün öğrenciler çalışmaya katılmışlardır. Araştırma sonucunda yabancı dil ders kaygısına yönelik görüşlerim cinsiyete göre ölçeğin yabancı dil ders kaygısı, dil dersinde konuşma kaygısı alt boyutları ve ölçeğin tamamı açısından kadın öğrenciler lehine istatistiksel olarak anlamlı düzeyde farklılaştığı belirlenmiştir. Etki büyüklükleri dikkate alındığında cinsiyetin bu boyutlardaki etkisinin “Güçlü” olduğu gözlenmiştir. Yabancılarla Konuşma Kaygısı açısından ise yazma, okuma ve main course akademik başarı puanları ile düşük, anlamlı olmayan ilişkiler gözlenmiştir. Genel eğilim yüksek ve düşük düzeydeki kaygının öğrenmeyi olumsuz etkilediği yönündedir. Bu araştırmada ise öğrencilerin akademik başarı puanlarının kaygı ile negatif yönde yüksek düzeyde bir ilişki içinde olduğu gözlenmiştir. Buna göre kaygının azalması ile akademik başarı puanları olumlu yönde arttırabilecektir. Bu ise teorik bağlam ile birlikte değerlendirildiğinde öğrencilerin ortalama düzeyde bir kaygı yaşadığı şeklinde değerlendirilebilir

The main purpose of this study is to evaluate the students’ views, receiving foreign language preparation education, in terms of course anxiety. The study was conducted according to the descriptive survey modal. In the study, a Scale Bearing English Course anxiety developed by Horwitz ,Horwitz and Cope(1986) and its validity and reliability analysis tested and adapted by Gürsu (2011) was used. Study’s universe was constituted with the undergraduate students, receiving foreign language preparation education at Higher School of Foreign Languages in Inonu University-Malatya. In this survey, the sample was not chosen, and data collection was gathered from all prep school participants present in their classes at the time of the research data collecting instruments were carried out. According to the statistical analysis of research’s findings, when foreign language course anxiety in class, and its sub-dimensions of speaking anxiety in foreign language class and its complete scale was put into consideration in terms of genders, a significant difference was identified in favor of women. When impact scales were regarded, genders conveying ‘a strong influence’ was observed in terms of those sub-dimensions. Non-significant correlations were observed in students’ academic achievement score related to reading writing and main course elements in terms of Speaking with Foreigners Anxiety. Anxiety was again determined in this research that had important influence as variables on learning and teaching processes. In general tendency, anxiety in high or low level has negative influence on learning and teaching. In this study, a negative correlation in high level was observed between anxiety and students’ academic achieved points. As a conclusion, by decreasing anxiety, learners’ academic achievement can, to certain extends, be increased. Briefly, when this situation was assessed together with theoretical aspect, we can come to the conclusion that students carried anxiety in an average level.
Relations Between Foreign Language Anxiety and Achievement of Foreign Language Preparatory Students